2022
DOI: 10.1159/000525341
|View full text |Cite
|
Sign up to set email alerts
|

Sotorasib Shows Intracranial Activity in Patients with <b><i>KRAS G12C-</i></b>Mutated Adenocarcinoma of the Lung and Untreated Active Brain Metastases

Abstract: Treatment with sotorasib has shown intracranial complete responses and continued intracranial stabilization in <i>KRAS G12C-</i>mutated non-small-cell lung carcinoma (NSCLC) patients with previously treated, stable brain metastases in a post hoc analysis of the ongoing CodeBreaK 100 trial. We present the case of a patient with <i>KRAS G12C-</i>mutant adenocarcinoma of the lung with active untreated brain metastases with a nearly complete intracranial response only 6 weeks after start of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The safety and tolerability profile seen in this cohort, with the most common CNS-specific TRAEs reported being dysgeusia and dizziness, was broadly consistent with previous reports from the KRYSTAL-1 trial. 14,21 No other KRAS G12C inhibitor has previously demonstrated IC activity in a prospective clinical trial, although case studies [22][23][24] and post hoc analyses from registrational data sets 13,25 have demonstrated IC responses with sotorasib and adagrasib. However, the post hoc analyses from both sotorasib and adagrasib required adequately treated CNS metastases including radiation before enrollment, leading to an inability to fully interpret the IC activity of the KRAS G12C inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and tolerability profile seen in this cohort, with the most common CNS-specific TRAEs reported being dysgeusia and dizziness, was broadly consistent with previous reports from the KRYSTAL-1 trial. 14,21 No other KRAS G12C inhibitor has previously demonstrated IC activity in a prospective clinical trial, although case studies [22][23][24] and post hoc analyses from registrational data sets 13,25 have demonstrated IC responses with sotorasib and adagrasib. However, the post hoc analyses from both sotorasib and adagrasib required adequately treated CNS metastases including radiation before enrollment, leading to an inability to fully interpret the IC activity of the KRAS G12C inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of sotorasib in NSCLC patients with untreated CNS metastases remains anecdotal despite several case reports ( 17 - 20 ) as CodeBreak studies published to date limited enrollment to NSCLC patients with treated brain metastases. Nonetheless, it is reassuring to see that in the pre-planned exploratory analysis of CB200 among those with known CNS metastases (sotorasib, n=58; docetaxel, n=60), median time to recurrence of CNS disease was delayed with sotorasib compared to docetaxel (15.8 vs. 10.5 months; HR, 0.52; 95% CI: 0.26–1.03), likely reflecting the effect of superior extracranial disease control but also indirectly raising the possibility of CNS activity as well that needs to be prospectively characterized and confirmed.…”
Section: How About Brain Metastases?mentioning
confidence: 99%
“…Adagrasib, a second covalent inhibitor of KRAS-G12C, offers a longer half-life than sotorasib and demonstrated a comparable intracranial PFS of 5.4 months in patients with stable brain metastases [105]. The intracranial activity of sotorasib and adagrasib against untreated, active brain metastases is also suggested in case reports and preliminary findings from the KRYSTAL-1 study (NCT03785249) [106,107].…”
Section: Kras Inhibitorsmentioning
confidence: 99%